Copper‐Catalyzed [2+2+2] Modular Synthesis of Multisubstituted Pyridines: Alkenylation of Nitriles with Vinyliodonium Salts. (28th March 2017) - Sheng, Jinyu; Wang, Yong; Su, Xiang; He, Ru; Chen, Chao
Abstract: A [2+2+2] modular synthesis of multisubstituted pyridines, with excellent regioselectivity, has been realized by copper catalysisand involves three distinct components: vinyliodonium salts, nitriles, and alkynes. The reactions proceeded with the facile formation of an aza‐butadienylium intermediate by alkenylation of the nitrile with a vinyliodonium salt. Moreover, the alkynes in the reaction were extended to alkenes, which are an advantage of expense and relative scarceness of alkynes.